Full circumpolar migration ensures evolutionary unity in the Emperor penguin - Robin Cristofari (Nature Portfolio, 2016)
Delimiting populations is crucial for conserving threatened species. Using genome-wide data from the whole of Antarctica, Cristofari et al.show that Emperor penguins are organised into a single global population that have shared demography since the late Quarternary.